Language Ability of Students With Emotional Disturbance: Discrepancies Between Teacher Ratings and Direct Assessment. (March 2018) - Chow, Jason C.; Hollo, Alexandra
Language impairment often goes unidentified in students with behavioral disorders, perhaps in part because different forms of problem behavior deflect adult attention from more subtle language deficits. Therefore, attention to teachers' perception of students' language and behavioral performance is merited. The present study examines agreement between a norm-referenced adult rating scale of language proficiency and a standardized, comprehensive language assessment in a sample of 43 boys identified with emotional disturbance (ED). Results of this preliminary study showed low agreement between direct assessment and teacher ratings of language, and that measures of language varied relative to behavioral profiles.